2015
DOI: 10.4103/2229-5151.158392
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of venous collapsibility and central venous pressure during standardized crystalloid bolus: A prospective, observational, pilot study

Abstract: Introduction:Measurement of intravascular volume status is an ongoing challenge for physicians in the surgical intensive care unit (SICU). Most surrogates for volume status, including central venous pressure (CVP) and pulmonary artery wedge pressure, require invasive lines associated with a number of potential complications. Sonographic assessment of the collapsibility of the inferior vena cava (IVC) has been described as a noninvasive method for determining volume status. The purpose of this study was to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…[22] Intensivist–performed focused bedside sonographic assessment of intravascular volume status is increasing in popularity due to its relative simplicity, skill standardization, and mounting evidence of clinical utility. [910121322232425] Given these parallel developments, as well as the need for more evidence–based comparative research, we set out to examine the relationship between IVC-CI and PAPs in a modest sample of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Intensivist–performed focused bedside sonographic assessment of intravascular volume status is increasing in popularity due to its relative simplicity, skill standardization, and mounting evidence of clinical utility. [910121322232425] Given these parallel developments, as well as the need for more evidence–based comparative research, we set out to examine the relationship between IVC-CI and PAPs in a modest sample of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[3] With declining the use of indwelling intravascular monitoring devices, including the pulmonary artery catheter (PAC),[45] search continues for reliable, accessible, and easy-to-use minimally invasive hemodynamic monitoring alternatives. [678] Although the correlation between inferior vena cava collapsibility index (IVC-CI) and central venous pressures (CVP) has been well described,[9101112] little information exists regarding the relationship between central vein collapsibility (including pertinent subcomponent measurements) and pulmonary artery pressures (PAPs). [1314] The aim of this study is to answer important questions regarding correlations between information traditionally provided by the PAC and the corresponding IVC-CI findings.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that an IV bolus tends to produce an early response in IVC, while the CVP response is more gradual [47]. However, other studies have shown that bedside ultrasonographic measurement of the inferior vena cava fails to predict fluid responsiveness in the first 6 hours after cardiac surgery [48] and hemodynamic response to early hemorrhage [49].…”
Section: Ivc Collapsibility Indexmentioning
confidence: 99%
“…Within 20 years of its initial clinical use, scientists had advanced the technology to a point where ultrasound machines were much more compact and offered image quality sufficient to evaluate the fetus in obstetrics care [4]. Since then, diagnostic applications of sonography have incrementally increased to encompass literally every field of health care, from physical medicine and rehabilitation to obstetrics and gynecology, emergency medicine to pulmonology, critical care to disaster management, oncology to trauma and emergency surgery, and pediatrics to gastroenterology [5][6][7][8][9][10].As clinical applications of ultrasound have expanded and image resolution has improved, the actual sizes of machines and probes have progressively become smaller [11][12][13]. This portability has allowed ultrasound studies to occur at a patient's bedside, largely eliminating the need for * S. P. Stawicki…”
mentioning
confidence: 99%
“…Within 20 years of its initial clinical use, scientists had advanced the technology to a point where ultrasound machines were much more compact and offered image quality sufficient to evaluate the fetus in obstetrics care [4]. Since then, diagnostic applications of sonography have incrementally increased to encompass literally every field of health care, from physical medicine and rehabilitation to obstetrics and gynecology, emergency medicine to pulmonology, critical care to disaster management, oncology to trauma and emergency surgery, and pediatrics to gastroenterology [5][6][7][8][9][10].…”
mentioning
confidence: 99%